Pengaruh Etos Kerja dan Karateristik Individu Terhadap Kinerja Pegawai Puskesmas Prambon - Mido Sekarningrum; Bambang Suwarsono; Nurali Agus Najibul Zamzam (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The background of this research is that in an institution engaged in the health sector, because in an institution human resources are very important in achieving success. The aim of this research is to explain the influence of work ethic and individual characteristics on employee performance. This research uses purposive sampling. The sample in this study was 41 employees from a population of 71 Prambon Health Center employees. In this study, the results showed that work ethic and individual characteristics partially had a significant effect on the performance of Prambon Health Center employees. While simultaneously the two variables have a significant effect on the performance of Prambon Health Center employees.